2016
DOI: 10.1007/s11356-016-6087-5
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen microprofile in the prepared sediments and its implication for the sediment oxygen consuming process in a heavily polluted river of China

Abstract: Dissolved oxygen (DO) microprofiles of prepared sediments from 24 sampling sites in the Fuyang River were measured using a gold amalgam microelectrode in this study. The measured microprofiles can be divided into four types. In type I profiles, DO kept constant in the overlying water and decreased smoothly in the pore water; in type II profile, DO showed fluctuation in the pore water; in type III profiles, DO showed peak in the SWI; in type IV profiles, DO decreased obviously in the overlying water. Type I pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Gimiplasmatales might not respire oxygen. It was found that the penetration depth of oxygen into the polluted sediments was usually limited within few millimetres even the overlying water was oxygen saturated (Wang et al ., 2016), providing an anaerobic condition for the growth of Ca . Gimiplasmatales.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gimiplasmatales might not respire oxygen. It was found that the penetration depth of oxygen into the polluted sediments was usually limited within few millimetres even the overlying water was oxygen saturated (Wang et al ., 2016), providing an anaerobic condition for the growth of Ca . Gimiplasmatales.…”
Section: Resultsmentioning
confidence: 99%
“…sediments was usually limited within few millimetres even the overlying water was oxygen saturated (Wang et al, 2016), providing an anaerobic condition for the growth of Ca. Gimiplasmatales.…”
Section: Fig 2 Amentioning
confidence: 99%